The argumentation in workplace accident trials. The case of the civil court of Mons (1870-1904) - Bruno Debaenst (Clio@Themis, 2021)
At the end of the nineteenth century, workplace accident trials increased significantly in number in Belgium and in other European countries. These cases are interesting, as they have a hybrid character, with a unique blend of industrial and legal argumentation. The article focuses on 293 cases from the civil court of Mons, from the period 1870 till 1904, in order to analyze this specific argumentation.